Technological Innovations in Auditing: A Systematic Literature Review on the Use of AI and Digitalization - Lubis, Porkas Sojuangon; Kesuma, Sambas Ade; Muda, Iskandar (Journal of Business and Behavioural Entrepreneurship, 2025)
This study explores the adoption of Artificial Intelligence (AI), Blockchain, and Robotic Process Automation (RPA) in the field of auditing, focusing on their impact on audit efficiency and transparency. The main issue addressed is how these emerging technologies can transform traditional auditing practices and the challenges related to their integration. The objective is to examine the benefits and challenges associated with the implementation of these technologies and how they can enhance the accuracy, transparency, and speed of audits. The research employs a systematic literature review (SLR) method, analyzing findings from 33 studies to synthesize key insights into the adoption of AI, Blockchain, and RPA in auditing. Key findings reveal that AI enhances decision-making and data analysis, Blockchain ensures data integrity and transparency, and RPA automates routine tasks, improving the overall audit process. The research identifies challenges, including ethical concerns, high implementation costs, and the need for skilled professionals. In conclusion, while these technologies offer significant improvements in auditing, successful adoption requires overcoming barriers such as regulatory challenges, data privacy issues, and ensuring adequate training for auditors.